Hydrological pattern of Pahang River basin and their relation to flood historical event - Pan, Ia Lun; Muhd. Barzani Gasim; Mohd. Ekhwan Toriman; Sahibin Abd. Rahim; Khairul Amri Kamaruddin (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2011)
Pahang River is the main channel to drain off water from the inundated area of Pahang Basin to the South China Sea during wet season which is caused by the northeast monsoon. Most of the inundations of lower areas of Pahang River Basin were caused by overflowing of the Pahang River. The statistics of rainfall and hydrological factors were calculated in terms of their means for the period from 1980 to 2009. The highest water level recorded at Sg. Yap was 45.36m and the lowest was 43.49m, whereas for Temerloh, the highest water level was 26.71m and the lowest was 24.73m. Lubuk Paku had the highest water level of 15.23m and the lowest was recorded as 12.70m. Besides that, the highest monthly total rainfall at Sg.Yap was 254.01mm and the lowest was 106.67mm. At Temerloh, the highest monthly total rainfall was 219.83mm and the lowest was 93.75mm. At Lubuk Paku, the highest monthly total rainfall was 324.57mm and the lowest was 79.81mm. The mean discharge of Pahang River (1980-2009) at Sg. Yap was 845.78m³/s, at Temerloh was 1008.50m³/s and Lubuk Paku was 1184.46m³/s. The water levels which beyond the danger level in recent three decades had also been identified.